BLASPHEMY LAWS IN MUSLIM COUNTRIES - Zaryab Khan; Dr. Tansif Ur Rehman; Sher Afghan; Abdullah Mandokhail (International Journal of Contemporary Issues in Social Sciences, 2024)
Blasphemy laws in Muslim-majority countries have garnered significant attention due to their impact on freedom of expression and religious pluralism. These laws typically prohibit speech or actions deemed disrespectful or offensive to Islam, its Prophet, or sacred symbols. Implementation varies widely among countries, ranging from fines and imprisonment to the death penalty. These laws intersect with broader socio-political dynamics, including authoritarianism, sectarian tensions, and struggles for power. They raise questions about the balance between religious sensitivities and fundamental human rights, such as freedom of speech and belief. Recent cases, like the controversy surrounding Asia Bibi in Pakistan, have sparked international outcry and debates over the reform or abolition of blasphemy laws in these contexts. Understanding these laws’ origins, effects, and implications is crucial for navigating the intersection of religion, law, and human rights in Muslim-majority societies.